Ti-W-Al homogeneous solid solution alloy material and preparation method thereof

By combining low-energy ball mill and high-energy ball mill, the W/Ti interface is eliminated and the W element is uniformly diffused in the Ti matrix, solving the problem of unhomogeneity of Ti-W alloys in the prior art, and a Ti-W-Al homogeneous solid solution alloy material with excellent mechanical properties is prepared.

CN119800151APending Publication Date: 2025-04-11NORTH CHINA ELECTRIC POWER UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510023001.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

It is difficult to prepare homogeneous Ti-W solid solution alloy materials in the prior art, resulting in uneven β-Ti phase regions and Ti/W interfaces in the alloy, affecting the mechanical properties.

Method used

The method of combining low-energy ball mill and high-energy ball mill is adopted to eliminate the W/Ti interface and achieve uniform diffusion of W elements in the Ti matrix through vacuum drying and high-vacuum and high-temperature dehydrogenation. Then, the sintering is performed using a discharge plasma sintering system to prepare a homogeneous Ti-W-Al solid solution alloy material.

Benefits of technology

The homogeneous solid solution structure of Ti-W-Al alloy is realized, eliminating the uneven β-Ti phase region and Ti/W interface, significantly improving the mechanical properties and production efficiency of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800151A_ABST
    Figure CN119800151A_ABST
Patent Text Reader

Abstract

The invention discloses a Ti-W-Al homogeneous solid solution alloy material and a preparation method thereof. The preparation method comprises the following steps: firstly, weighing titanium powder, tungsten powder and aluminum powder according to the mass percent, and carrying out low-energy ball milling to obtain uniformly mixed powder; then the mixed powder is subjected to high-energy ball-milling mechanical alloying, and Ti-W-Al alloyed powder is obtained; then carrying out high-vacuum high-temperature dehydrogenation treatment on the mechanically alloyed powder; and finally, the alloyed powder is put into a graphite mold, a spark plasma sintering system is used for sintering the alloyed powder, and the bulk Ti-W-Al homogeneous solid solution alloy material is obtained. The alloy system provided by the invention is relatively simple, the material stability and controllability are high, the raw material price is low, meanwhile, the preparation process route is relatively simple, the solid solution alloy with a uniform structure can be obtained without long-time heat treatment and thermoplastic deformation, the production efficiency can be effectively improved, the production cost is reduced, and industrial application is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal alloy materials, and more particularly to a Ti-W-Al homogeneous solid solution alloy material and a preparation method thereof. Background Art

[0002] Titanium alloy has the characteristics of low density, high specific strength and strong corrosion resistance, especially its specific strength ranks first among commonly used metal materials in the temperature range of -253 to 600℃. Titanium alloy materials have been widely used in aerospace, biomedicine, chemical industry, vehicles and other industrial fields.

[0003] Commonly used alloying elements in titanium alloys can be divided into three categories. One category is α-stabilizing elements that can stabilize the room temperature α phase, such as aluminum (Al); the other category is β-stabilizing elements that can stabilize the high temperature β phase, such as molybdenum (Mo), vanadium (V), iron (Fe), chromium (Cr), niobium (Nb), etc.; and the other category is neutral elements, such as zirconium (Zr), tin (Sn), etc. In recent years, studies have shown that tungsten (W) is also a very promising alloying element for Ti. For example, the experimental results of Choe et al. show that the Ti-W alloy formed by adding 7.5-15wt.% W particles to pure titanium has good quasi-static tensile / compressive mechanical properties and wear resistance. Frary et al. found that the quasi-static mechanical properties of the Ti-W alloy containing 10wt.% tungsten particles are comparable to the mechanical properties of the commonly used titanium alloy Ti-6Al-4V (TC4). Wang et al.'s research shows that after adding a small amount (5wt.%) of W particles to the TC4 alloy, its quasi-static tensile strength and plasticity are improved.

[0004] However, due to the significant differences in melting points and densities between Ti and W, it is almost impossible to prepare homogeneous Ti-W solid solution alloy materials using traditional liquid phase metallurgy or powder metallurgy methods. Therefore, the so-called "Ti-W alloys" in the above studies are actually titanium-based composite materials reinforced by W particles. The W element exists in the Ti matrix in the form of single particles, and only around the W particles there is an extremely uneven β-Ti phase region with a width of microns formed by W / Ti interdiffusion. At this time, the Ti / W interface that must exist in the alloy, as well as the size and dispersion uniformity of the W particles, will seriously affect the mechanical properties of the material. For example, Choe et al. found that as the size of the W particles increased, the quasi-static mechanical properties of the Ti-W alloy (titanium-based composite material) continued to decline. The research of Na Li et al. shows that although a relatively uniform Ti-W solid solution alloy can be obtained through solution treatment after hot isostatic pressing sintering, it needs to be kept warm for a long time (5h) at high temperature (1400℃), which leads to low production efficiency; and long-term heat preservation at high temperature will cause coarse alloy grains and reduce the mechanical properties of the material. Therefore, post-deformation treatment such as hot extrusion is required to make the Ti-W solid solution alloy have better mechanical properties. Summary of the invention

[0005] In view of this, the present invention provides a novel Ti-W-Al homogeneous solid solution alloy material and a preparation method thereof to overcome the defects of the prior art and enable the alloy material to have better comprehensive mechanical properties.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] Firstly, the present invention provides a Ti-W-Al homogeneous solid solution alloy material, which comprises the following components in mass percentage: 5%-25% W, 0%-6% Al, and the balance Ti.

[0008] When the W content exceeds 25wt.%, the theoretical density of the Ti-W alloy will be greater than 5.5g / cm 3 , exceeding the density of most conventional titanium alloys, making them lose the lightweight characteristics of titanium materials; when the Al content exceeds 6wt.%, a TiAl intermetallic compound brittle phase may be formed in the titanium alloy. Therefore, preferably, the mass percentage content of W is controlled to 5-25wt.% in the present invention; the mass percentage content of Al is controlled to 0-6wt.%, and the rest is Ti; the content of impurity elements Fe≤0.3wt.%, O≤0.2wt.%, C≤0.06wt.%, N≤0.05wt.%, and H≤0.015wt.%.

[0009] The present invention further specifically provides a method for preparing the Ti-W-Al homogeneous solid solution alloy material described in the above technical solution, comprising the following steps:

[0010] (1) weighing titanium powder, tungsten powder and aluminum powder according to mass percentage and mixing them by low-energy ball milling to obtain a uniform slurry, and then vacuum drying the slurry to obtain a mixed powder in which Ti, W and Al powder particles are uniformly dispersed;

[0011] (2) subjecting the mixed powder to high-energy ball milling mechanical alloying and then passing through a 200-mesh sieve to obtain Ti-W-Al mechanical alloying powder;

[0012] (3) subjecting the mechanically alloyed Ti-W-Al powder to high vacuum and high temperature dehydrogenation treatment;

[0013] (4) placing the dehydrogenated alloyed powder into a graphite mold, and sintering the alloyed powder using a spark plasma sintering system, to obtain a bulk Ti-W-Al homogeneous solid solution alloy material after sintering.

[0014] Preferably, the titanium powder particles in step (1) are spherical, with a particle size of ≤25 μm and a purity of 99.9%; the tungsten powder particles are irregular polygons, with a particle size of 3 μm and a purity of 99.9%; and the aluminum powder particles are spherical, with a particle size of ≤25 μm and a purity of 99.9%.

[0015] Preferably, the low-energy ball milling process parameters in step (1) are: the process control agent is anhydrous ethanol, the total mass ratio of the grinding balls to the total mass of the W powder, Al powder and Ti powder is (5-8): 1, the rotation speed is 150-250r / min, the ball milling time is 1-2h, and before ball milling, the inside of the ball mill is evacuated by a vacuum pump to a pressure less than 2Pa.

[0016] Preferably, the process parameters of high-energy ball milling mechanical alloying in step (2) are: the process control agent is CaH2, the ratio of the total mass of the grinding balls to the total mass of the W powder, Al powder and Ti powder is (30-50):1, the rotation speed is 400-500r / min, the ball milling time is 1-3h, and before ball milling, the inside of the ball mill is evacuated to a vacuum using a vacuum pump, and then 1atm high-purity argon is filled in to provide atmosphere protection for the ball milling process.

[0017] Preferably, the process parameters of high vacuum and high temperature dehydrogenation treatment in step (3) are: vacuum degree ≤ 10 -4 Pa, the dehydrogenation temperature is 600℃, and the holding time is 1-2h.

[0018] Preferably, the sintering process parameters of step (4) are: heating rate of 100°C / min, sintering temperature of 1100-1200°C, sintering pressure of 40-50MPa, and heat and pressure holding time of 15-20min.

[0019] It can be seen from the above technical solutions that, compared with the prior art, the present invention discloses a Ti-W-Al homogeneous solid solution alloy material and a preparation method thereof, which has the following beneficial effects:

[0020] According to the Ti-W binary phase diagram, W and Ti are infinitely miscible, and no hard and brittle intermetallic compound phase will be formed under any solid solubility conditions. Therefore, using W as an alloying element for Ti can achieve a good solid solution strengthening effect without introducing harmful phases into the alloy, which has obvious advantages. At the same time, the melting point of W ranks first among common substances, and using W as an alloying element for Ti can also improve the high temperature performance of titanium alloys. In addition, adding a small amount of Al to the alloy can reduce the density of the alloy, increase its specific strength, and also produce a certain solid solution strengthening effect.

[0021] W is a β-phase stabilizing element of Ti, and the type of titanium alloy can be easily adjusted by changing the W content. For example, when the W content is 5wt.%, the obtained titanium alloy is a nearly α-type alloy, when the W content is 5-20wt.%, the obtained titanium alloy is an α+β-type alloy, and when the W content is greater than 20wt.%, the obtained titanium alloy is a nearly β-type alloy.

[0022] By using high-energy ball milling mechanical alloying followed by spark plasma sintering, the W element in the form of single particles in the Ti matrix can be completely eliminated in a relatively short period of time (more than ten minutes), thus avoiding the formation of a W / Ti interface. At the same time, the W element can be evenly diffused and distributed in the Ti matrix, thus avoiding alloy element segregation and grain growth, thereby obtaining a homogeneous Ti-W-Al solid solution alloy material with fine grains.

[0023] Using CaH2 as a process control agent for high-energy ball milling mechanical alloying can effectively avoid the problem of introducing a large amount of difficult-to-remove impurities such as C and O into the alloying powder when using conventional process control agents such as stearic acid, while ensuring a high alloying powder yield. The H impurities introduced when using CaH2 can be removed by subsequent high-vacuum and high-temperature dehydrogenation treatment, thereby ensuring the high purity of the mechanically alloyed powder.

[0024] The alloy system proposed in the present invention is relatively simple, and the material stability and controllability are strong. Compared with alloy elements such as V, Nb, and Zr, W and Al are cheap. At the same time, the preparation process route is relatively simple, and a solid solution alloy with uniform structure can be obtained without long-term heat treatment and thermoplastic deformation, which can effectively improve production efficiency and reduce production costs, and is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0026] Figure 1 This is a scanning electron microscope photograph of the Ti-15W alloy powder after mechanical alloying and vacuum high-temperature dehydrogenation treatment in Example 2;

[0027] Figure 2 This is a scanning electron microscope photograph of the Ti-5W-6Al alloy powder after mechanical alloying and vacuum high-temperature dehydrogenation treatment in Example 4;

[0028] Figure 3 XRD phase analysis spectra of Ti-W and Ti-W-Al solid solution alloys prepared in Examples 1 to 5;

[0029] Figure 4-8 The following are scanning electron microscope photographs of the microstructures of the solid solution alloys prepared in Examples 1 to 5, respectively. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In the following embodiments, the Ti powder particles are spherical, with a particle size of ≤25 μm and a purity of 99.9%; the W powder particles are irregular polygons, with a particle size of 3 μm and a purity of 99.9%; and the Al powder particles are spherical, with a particle size of ≤25 μm and a purity of 99.9%.

[0032] The graphite mold is cylindrical and consists of a male mold, a female mold, a gasket, etc. The inner diameter of the female mold (i.e., the sample diameter) is 30 mm.

[0033] Example 1

[0034] Preparation of Ti-5W solid solution alloy

[0035] (1) 1.5 g of W powder and 28.5 g of Ti powder were placed in a ball mill, and 150 g of grinding balls were added, with a ball-to-material ratio of 5:1; anhydrous ethanol was then injected until the material and the grinding balls were completely covered, the ball mill was sealed and the inside of the ball mill was evacuated to a pressure of ≤2 Pa using a vacuum pump; low-energy ball milling was then performed at a speed of 150 r / min for 1 h to obtain a composite slurry; the slurry was then vacuum dried to obtain a Ti and W mixed powder;

[0036] (2) 30 g of Ti-5W powder mixed evenly by low-energy ball milling was placed in a ball mill again, and 900 g of grinding balls were added, with a ball-to-material ratio of 30:1; then 0.6 g of CaH2 powder was added, the ball mill was sealed and the inside of the ball mill was evacuated by a vacuum pump and filled with 1 atm high-purity argon as a protective atmosphere; then high-energy ball milling was performed at a speed of 400 r / min for 1 h; then sieved with a 200-mesh sieve to obtain Ti-5W alloyed powder;

[0037] (3) Place the Ti-5W alloyed powder in a high vacuum heat treatment system and evacuate the system to a pressure of ≤10 -4 Pa, then kept at 600°C for 2h and then cooled to room temperature and taken out;

[0038] (4) The dehydrogenated alloyed powder was placed in a graphite mold, and then the mechanical alloyed powder was densified and sintered using a spark plasma sintering system to obtain a bulk Ti-5W homogeneous solid solution alloy. The sintering process parameters were: heating rate of 100°C / min, sintering temperature of 1100°C, sintering pressure of 40 MPa, and holding time of 15 min.

[0039] Example 2

[0040] Preparation of Ti-15W solid solution alloy

[0041] (1) 4.5 g of W powder and 25.5 g of Ti powder were placed in a ball mill, and 180 g of grinding balls were added, with a ball-to-material ratio of 6:1; anhydrous ethanol was then injected until the material and the grinding balls were completely covered, the ball mill was sealed, and the inside of the ball mill was evacuated to a pressure of ≤2 Pa using a vacuum pump; low-energy ball milling was then performed at a speed of 150 r / min for 1.5 h to obtain a composite slurry; the slurry was then vacuum dried to obtain a Ti and W mixed powder;

[0042] (2) 30 g of Ti-15W powder that had been uniformly mixed by low-energy ball milling was placed in a ball mill again, and 1200 g of grinding balls were placed in the ball mill, with a ball-to-material ratio of 40:1; then 0.3 g of CaH2 powder was added, the ball mill was sealed and the inside of the ball mill was evacuated by a vacuum pump and filled with 1 atm of high-purity argon as a protective atmosphere; then high-energy ball milling was performed at a speed of 450 r / min for 2 h; then the powder was sieved with a 200-mesh sieve to obtain Ti-15W alloyed powder;

[0043] (3) Place the Ti-15W alloyed powder in a high vacuum heat treatment system and evacuate the system to a pressure of ≤10 -4 Pa, then kept at 600°C for 1h and then cooled to room temperature and taken out;

[0044] (4) The dehydrogenated alloyed powder was placed in a graphite mold, and then the mechanical alloyed powder was densified and sintered using a spark plasma sintering system to obtain a bulk Ti-15W homogeneous solid solution alloy. The sintering process parameters were: heating rate of 100°C / min, sintering temperature of 1100°C, sintering pressure of 40 MPa, and holding time of 15 min.

[0045] Example 3

[0046] Preparation of Ti-25W solid solution alloy

[0047] (1) 7.5 g of W powder and 22.5 g of Ti powder were placed in a ball mill, and then 240 g of grinding balls were added, with a ball-to-material ratio of 8:1; then anhydrous ethanol was injected until the materials and grinding balls were completely covered, the ball mill was sealed and the inside of the ball mill was evacuated by a vacuum pump to a pressure of ≤2 Pa; then low-energy ball milling was performed at a speed of 250 r / min for 2 h to obtain a composite slurry; then the slurry was vacuum dried to obtain a Ti and W mixed powder;

[0048] (2) 30 g of Ti-25W powder mixed evenly by low-energy ball milling was placed in a ball mill again, and 1500 g of grinding balls were added, with a ball-to-material ratio of 50:1; then 0.3 g of CaH2 powder was added, the ball mill was sealed and the inside of the ball mill was evacuated by a vacuum pump and filled with 1 atm high-purity argon as a protective atmosphere; then high-energy ball milling was performed at a speed of 500 r / min for 3 h; then sieved with a 200-mesh sieve to obtain Ti-25W alloyed powder;

[0049] (3) Place the Ti-25W alloyed powder in a high vacuum heat treatment system and evacuate to a pressure of ≤10 -4 Pa, then kept at 600°C for 1h and then cooled to room temperature and taken out;

[0050] (4) The dehydrogenated alloyed powder was placed in a graphite mold, and then the mechanical alloyed powder was densified and sintered using a spark plasma sintering system to obtain a bulk Ti-25W homogeneous solid solution alloy. The sintering process parameters were: heating rate of 100°C / min, sintering temperature of 1200°C, sintering pressure of 50 MPa, and holding time of 20 min.

[0051] Example 4

[0052] Preparation of Ti-5W-6Al solid solution alloy

[0053] (1) 1.5 g W powder, 1.8 g Al powder and 26.7 g Ti powder were placed in a ball mill, and 180 g grinding balls were added, with a ball-to-material ratio of 6:1; anhydrous ethanol was then injected until the materials and grinding balls were completely covered, the ball mill was sealed and the inside of the ball mill was evacuated to a pressure of ≤2 Pa using a vacuum pump; low-energy ball milling was then performed at a speed of 150 r / min for 1.5 h to obtain a composite slurry; the slurry was then vacuum dried to obtain a Ti and W mixed powder;

[0054] (2) 30 g of Ti-5W-6Al powder that has been uniformly mixed by low-energy ball milling is placed in a ball mill again, and 1200 g of grinding balls are placed in the ball mill, with a ball-to-material ratio of 40:1; then 0.6 g of CaH2 powder is added, the ball mill is sealed and the inside of the ball mill is evacuated by a vacuum pump and filled with 1 atm high-purity argon as a protective atmosphere; then high-energy ball milling is performed at a speed of 400 r / min for 1.5 h; then the powder is sieved with a 200-mesh sieve to obtain Ti-5W-6Al alloyed powder;

[0055] (3) Place the Ti-5W-6Al alloyed powder in a high vacuum heat treatment system and evacuate the system to a pressure of ≤10 -4 Pa, then kept at 600°C for 2h and then cooled to room temperature and taken out;

[0056] (4) The dehydrogenated alloyed powder was placed in a graphite mold, and then the mechanical alloyed powder was densified and sintered using a spark plasma sintering system to obtain a bulk Ti-5W-6Al homogeneous solid solution alloy. The sintering process parameters were: heating rate of 100°C / min, sintering temperature of 1100°C, sintering pressure of 40 MPa, and holding time of 15 min.

[0057] Example 5

[0058] Preparation of Ti-15W-6Al solid solution alloy

[0059] (1) 4.5 g W powder, 1.8 g Al powder and 23.7 g Ti powder were placed in a ball mill, and 180 g grinding balls were added, with a ball-to-material ratio of 6:1; anhydrous ethanol was then injected until the materials and grinding balls were completely covered, the ball mill was sealed and the inside of the ball mill was evacuated to a pressure of ≤2 Pa using a vacuum pump; low-energy ball milling was then performed at a speed of 200 r / min for 1.5 h to obtain a composite slurry; the slurry was then vacuum dried to obtain a Ti and W mixed powder;

[0060] (2) 30 g of Ti-15W-6Al powder that had been uniformly mixed by low-energy ball milling was placed in a ball mill again, and 1200 g of grinding balls were placed in the ball mill, with a ball-to-material ratio of 40:1; then 0.3 g of CaH2 powder was added, the ball mill was sealed and the inside of the ball mill was evacuated by a vacuum pump and filled with 1 atm of high-purity argon as a protective atmosphere; then high-energy ball milling was performed at a speed of 450 r / min for 2 h; then the powder was sieved with a 200-mesh sieve to obtain Ti-15W-6Al alloyed powder;

[0061] (3) Place the Ti-15W-6Al alloyed powder in a high vacuum heat treatment system and evacuate the system to a pressure of ≤10 -4 Pa, then kept at 600°C for 1h and then cooled to room temperature and taken out;

[0062] (4) The dehydrogenated alloyed powder was placed in a graphite mold, and then the mechanical alloyed powder was densified and sintered using a spark plasma sintering system to obtain a bulk Ti-15W-6Al homogeneous solid solution alloy. The sintering process parameters were: heating rate of 100°C / min, sintering temperature of 1100°C, sintering pressure of 40MPa, and holding time of 15min.

[0063] Figure 1-2 The figure shows scanning electron microscope photos of Ti-15W (Example 2) and Ti-5W-6Al (Example 4) alloy powders after mechanical alloying and vacuum high-temperature dehydrogenation. It can be seen from the figure that the powder particle size after mechanical alloying is uniform, with a size of about 75μm; W particles (bright white particles) are embedded in the Ti matrix and are evenly distributed, and most of the W particles are broken into nano-scale particles, which is very beneficial for element diffusion and uniform solid solution in the subsequent sintering process; no Al particles are found, indicating that Al has been completely dissolved in the Ti matrix during the mechanical alloying process.

[0064] Figure 3 Shown are the XRD phase analysis spectra of the five Ti-W(-Al) alloys of Examples 1-5 after sintering. It can be seen from the figure that only α-Ti and β-Ti peaks exist in the five alloys, and the characteristic peaks of W single substance are not detected, indicating that Ti-W(-Al) solid solution alloys can be successfully prepared by mechanical alloying combined with spark plasma sintering; in addition, the β phase peak intensity (content) increases with the increase of W content.

[0065] Figure 4-8 The scanning electron microscope photos of the microstructures of the five solid solution alloys of Examples 1-5 are shown. It can be seen from the figure that Ti-5W is a near-α-type alloy, Ti-15W, Ti-5W-6Al and Ti-15W-6Al are α+β-type alloys, all of which have a dual-state structure, and as the W content increases, the amount of equiaxed α phase in the dual-state structure decreases, and the amount of β transition domains (β phases) increases, which is consistent with the XRD test results; the Ti-25W alloy structure is composed of equiaxed β grains and a small amount of intergranular α phase, which is a near-β-type alloy, and the average grain size of the β phase is about 3μm.

[0066] The room temperature quasi-static tensile mechanical property test results of the materials prepared in the above Examples 1 to 5 are shown in Table 1, and the room temperature quasi-static compression mechanical property test results are shown in Table 2. The mechanical property values ​​of two commonly used titanium alloys TC4 (α+β alloy) and TA15 (near α alloy) specified in the national standard GB / T2965-2007 are shown in Table 1.

[0067] Table 1 Room temperature quasi-static tensile mechanical properties test results of materials in Examples 1 to 5

[0068]

[0069] Table 2 Room temperature quasi-static compression mechanical properties test results of materials in Examples 1 to 5

[0070]

[0071]

[0072] It can be seen from Table 1-2 that the strength of the sintered new Ti-W-Al alloy is significantly higher than that of conventional titanium alloy, and its plasticity is comparable to that of conventional titanium alloy. Its performance can be further optimized through heat treatment or thermoplastic deformation, and it has great application potential.

[0073] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments, and the same and similar parts between the embodiments can be referred to each other. The above description of the disclosed embodiments enables professionals and technicians in this field to implement or use the present invention. Various modifications to these embodiments will be obvious to professionals and technicians in this field, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to these embodiments shown in this article, but will comply with the widest range consistent with the principles and novel features disclosed herein.

Claims

1. A Ti-W-Al homogeneous solid solution alloy material, characterized in that: Calculated by mass percentage, the composition includes: 5%-25% W, 0%-6% Al, and the balance is Ti.

2. A method for preparing the Ti-W-Al homogeneous solid solution alloy material according to claim 1, characterized in that: The following steps are involved: (1) weighing titanium powder, tungsten powder and aluminum powder according to mass percentage and mixing them by low-energy ball milling to obtain a uniform slurry, and then vacuum drying the slurry to obtain a mixed powder in which Ti, W and Al powder particles are uniformly dispersed; (2) subjecting the mixed powder to high-energy ball milling mechanical alloying and then passing through a 200-mesh sieve to obtain Ti-W-Al mechanical alloying powder; (3) subjecting the mechanically alloyed Ti-W-Al powder to high vacuum and high temperature dehydrogenation treatment; (4) placing the dehydrogenated alloyed powder into a graphite mold, and sintering the alloyed powder using a spark plasma sintering system, to obtain a bulk Ti-W-Al homogeneous solid solution alloy material after sintering.

3. The method for preparing a Ti-W-Al homogeneous solid solution alloy material according to claim 2, characterized in that: The titanium powder particles in step (1) are spherical, with a particle size of ≤25 μm and a purity of 99.9%; the tungsten powder particles are irregular polygons, with a particle size of 3 μm and a purity of 99.9%; and the aluminum powder particles are spherical, with a particle size of ≤25 μm and a purity of 99.9%.

4. The method for preparing a Ti-W-Al homogeneous solid solution alloy material according to claim 2, characterized in that: The low-energy ball milling process parameters in step (1) are as follows: the process control agent is anhydrous ethanol, the total mass ratio of the grinding balls to the total mass of the W powder, Al powder and Ti powder is (5-8):1, the rotation speed is 150-250r / min, the ball milling time is 1-2h, and before ball milling, the inside of the ball mill is evacuated to a pressure of less than 2Pa using a vacuum pump.

5. The method for preparing a Ti-W-Al homogeneous solid solution alloy material according to claim 2, characterized in that: The process parameters of high-energy ball milling mechanical alloying in step (2) are as follows: the process control agent is CaH2, the ratio of the total mass of the grinding balls to the total mass of the W powder, Al powder and Ti powder is (30-50):1, the rotation speed is 400-500r / min, the ball milling time is 1-3h, and before ball milling, the inside of the ball mill is evacuated to a vacuum using a vacuum pump, and then 1atm high-purity argon is filled in to provide atmosphere protection for the ball milling process.

6. The method for preparing a Ti-W-Al homogeneous solid solution alloy material according to claim 2, characterized in that: Step (3) high vacuum high temperature dehydrogenation treatment process parameters are: vacuum degree ≤ 10 -4 Pa, the dehydrogenation temperature is 600℃, and the holding time is 1-2h.

7. The method for preparing a Ti-W-Al homogeneous solid solution alloy material according to claim 2, characterized in that: The sintering process parameters of step (4) are: heating rate of 100°C / min, sintering temperature of 1100-1200°C, sintering pressure of 40-50MPa, and heat and pressure holding time of 15-20min.